Genre fission : a new discourse practice for cultural studies - Barr, Marleen S. (Iowa City : University of Iowa Press, 2000)
What do Amsterdam prostitutes, NASA astronauts, cross-dressing texts, and Star Trek characters have in common? In Genre Fission, Marleen Barr wittily and eccentrically revitalizes cultural and literary theory by examining the points where such vastly different categories meet, converge, and reemerge as something new.
"The Grand Mix" or Who Wears the White Hats When the Barbie Liberation Organization Strikes Back? -- Private Lives: Peaceful Coexistences -- Bridging the Dead Father's Canonical Divide: Max Apple, Saul Bellow, Edgar Allan Poe, and Lynn Redgrave Form a Textual Cross-Dresser Support Group -- "All Good Things": The End of Star Trek: The Next Generation, the End of Camelot, and the End of the Tale about Woman as Handmaid to Patriarchy-as-Superman -- Shutting the Bestial Mouth: Confessions of Male Clones and Girl Gangs -- Public Displays: Sexed Spectacles -- Night Watch in Amsterdam's Red Light District: Prostitutes/Dutch Windows/Utopian and Dystopian Gazes -- Los York/New Angeles: "New York, New York, a Helluva Town" Sings "I Wish They All Could Be California Girls" -- American Middle-Class Males Mark the Moon: Retrospectively Reading the Apollo Program or Lorena Bobbitt vs. the Saturn -- Premier Discourses: First Times -- Women "Churtening" via the Cha Cha: Ursula K. Le Guin and Hispanic-American Authors Write to the Same Rhythm -- Wrapping the Reichstag vs. Rapping Racism or "A Colored Kind of White People": Black/White/Jew/Gentile -- Playing with Time: The Holocaust as "A Different Universe of Discourse" -- Epilogue: Discourse as Black Hole, and as Liberated Light.
Includes bibliographical references (pages 249-261) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: American fiction -- 20th century -- History and criticism -- Theory, etc; Postmodernism (Literature) -- United States; United States -- Civilization -- 20th century; Postmodernism -- United States; Discourse analysis, Literary; Culture -- Philosophy; Literary form; Roman américain -- 20e siècle -- Histoire et critique -- Théorie, etc; Postmodernisme (Littérature) -- États-Unis.; Postmodernisme -- États-Unis.; Discours littéraire.; Culture -- Philosophie; Genres littéraires.; États-Unis -- Civilisation -- 20e siècle.; literary criticism; LITERARY COLLECTIONS -- Essays; LITERARY CRITICISM -- Semiotics & Theory; American fiction; Civilization; Culture -- Philosophy; Discourse analysis, Literary; Literary form; Postmodernism; Postmodernism (Literature); United States; 1900-1999; Criticism, interpretation, etc